PENGARUH KEMASAN TERHADAP KUALITAS DADIH SUSU SAPI - Miskiyah (Miskiyah); Wisnu Broto (Buletin Peternakan, 2011)
Dadih is a traditional dairy product obtained from a fermentation of buffalo milk and usually packed using bamboo. The usage of bamboo for dadih packaging has limitation in transportation and storage life. This study aimed to examine the effect of packaging material to dadih quality produced from cow milk during storage. Experimental design used at this study was Completely Randomized Design with Factorial pattern (7 x 7). The first factor is packaging material that are bamboo; cup plastic pp; flexypack packaging; clay; flexypack packaging (with evacuation from bamboo); clay (with evacuation from bamboo); cup plastic pp (with evacuation from bamboo). The second factor is storage time (0, 4, 8, 12, 16, 20, and 24 days). Result showed that best packaging to cow milk dadih is flexypack and cup plastic pp. Cow milk dadih that was packed in flexypack and cup plastic pp had storage life up to 24 days at cold temperature (refrigerator). From the perspective of economic, cup plastic pp packaging showed most efficientpackaging. Characteristic of cow milk dadih packaged in cup plastic pp were total of titratable acid 1,60%; pH 3,88; viscocity 351,43 cPs; total solid 14,75%; water content 85,25%; ash content 0,90%; protein content 2,43%; fat content3,68%; total of lactic acid bacteria (LAB) at 8 x 1011 CFUs/g. Total LAB at dadih packaged in other kinds of packaging were >108 CFUs/ml. Organoleptic test showed that cup plastic pp packaging had excellence in tidiness attribute andconsumption amenity. Meanwhile, curd of dadih packaged in bamboo and flexypack had excellent at color and aroma. Clay packaging had excellence in mouthfell and texture. In general, the first priority of dadih choosen by panelist was cow milk dadih packed in clay packaging, bamboo treatment to flexypack packaging, and bamboo treatment to cup plastic pp.(Keyword: Dadih, Packaging, Quality)